Estimación de sexo a través de las estructuras dentales: Scoping Review (2022)
Sex estimation is important to determine the biological profile of human skeletal remains, contributing to the identification, it is essential to determine other traits such as age, ancestry or stature. There is a great variety of methods that use structures such as the pelvis and the skull, when these structures are not present; teeth are used since these structures are preserved in the face of different changes, even after death